2022
DOI: 10.1002/aelm.202200158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aromatic Solvents Residuals on Electron Mobility of Organic Single Crystals

Abstract: Ideally, balanced transport for both hole and electron carriers is favored in these double-carrier devices. But in actual, there is still a big lag between the electron and hole transport properties. For instance, the extremely high hole mobility has reached much more than 20 cm 2 V −1 s −1 , [10][11][12][13][14] but in sharp contrast, very few literatures have reported electron mobility beyond 10 cm 2 V −1 s −1 . [15][16][17][18][19] Understanding the determining factors that limit the charge mobility, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…From the results shown in Figure 1a-d and Figure S2, Supporting Information, electron transport characteristic was observed, thanks to the suppression of polar species by the PMMA layer and the nonpolar hexane solvent. [29][30][31]35,36] However, the electron mobility (0.04 ± 0.06 cm 2 V −1 s −1 ) was still significantly lower than the hole mobility (1.42 ± 0.56 cm 2 V −1 s −1 ). With such unbalanced ambipolar performance, these OFETs are hardly applicable to complementary circuits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the results shown in Figure 1a-d and Figure S2, Supporting Information, electron transport characteristic was observed, thanks to the suppression of polar species by the PMMA layer and the nonpolar hexane solvent. [29][30][31]35,36] However, the electron mobility (0.04 ± 0.06 cm 2 V −1 s −1 ) was still significantly lower than the hole mobility (1.42 ± 0.56 cm 2 V −1 s −1 ). With such unbalanced ambipolar performance, these OFETs are hardly applicable to complementary circuits.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27,28 ] By properly eliminating the adverse effects of polar species including polar or aromatic solvent residue and interfacial hydroxyl groups, electron transport with mobility over 10 –2 cm 2 V −1 s −1 was apparently observed. [ 29–31 ] However, compared with the high hole mobility, the electron mobility was still lower by one to two orders of magnitude, which is not ideal for practical ambipolar OFETs. Recent studies have shown that the apparent mobility of OFETs, apart from the intrinsic properties, can also be severely limited by the high contact resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inevitably raises the concern of improperly removing the solvent from the polymer before obtaining its final structure. It has been shown that the incorrect removal of the solvent affects both the physical and chemical properties of polymers [8][9][10][11]. For example, J.…”
Section: Introductionmentioning
confidence: 99%